2002
DOI: 10.1002/ddr.10151
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ginkgo biloba extract (EGb 761) on gene expression: Possible relevance to neurological disorders and age‐associated cognitive impairment

Abstract: Ginkgo biloba leaf extract (EGb 761), which contains many constituents, including flavonoid glycosides and terpenoids (ginkgolides, bilobalide), is used to treat cerebrovascular and peripheral vascular insufficiency, as well as cognitive impairment and other symptoms of dementia. Recent studies have indicated that these therapeutic effects of EGb 761 probably involve modification of the expression of many genes by actions involving several of its active constituents. As examples: EGb 761 and its ginkgolide B c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 171 publications
2
25
0
Order By: Relevance
“…Neuroprotection by EGb 761 is known as a "multipotent" action (i.e., it is achieved by modulating a variety of biological pathways simultaneously because of its complex nature) (DeFeudis, 2002;Smith and Luo, 2003). We next asked whether the inhibitory effect on oligomerization by an individual constituent is sufficient to correlate with its alleviative effect on A␤-induced paralysis.…”
Section: Egb 761 Modulates A␤ Oligomers In the Transgenic C Elegansmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroprotection by EGb 761 is known as a "multipotent" action (i.e., it is achieved by modulating a variety of biological pathways simultaneously because of its complex nature) (DeFeudis, 2002;Smith and Luo, 2003). We next asked whether the inhibitory effect on oligomerization by an individual constituent is sufficient to correlate with its alleviative effect on A␤-induced paralysis.…”
Section: Egb 761 Modulates A␤ Oligomers In the Transgenic C Elegansmentioning
confidence: 99%
“…Currently, a National Institutes of Health-supported GEM (Ginkgo Evaluation of Memory) study in the United States and a GuidAge study in Europe are underway to evaluate EGb 761 as a preventive drug (DeKosky et al, 2006). Substantial experimental data indicate that EGb 761 has neuroprotective and neuromodulatory effects (Luo, 2001;Watanabe et al, 2001;Yao et al, 2001;DeFeudis, 2002). Two of its major constituents, flavonoids (24%) and terpenoids (6%), have been actively investigated for their neuroprotective properties (DeFeudis, 1998;Smith and Luo, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…47, 48 EGb 761 has been shown to alter expression of a number of host genes. 49 Recent cDNA microarray stud- For NO experiments, primary astrocytes were prepared and exposed to Dox (5 g/ml) for 3 days, and the culture supernatants were collected to determine NO production using a Griess assay. Distilled H 2 O with the same pH was used as the control (Ϫ).…”
Section: Regulation Of Gfap Expression In Astrocytes By Egb 761mentioning
confidence: 99%
“…Numerous studies have shown that EGb 761 can counteract the detrimental effects of oxidative damage caused by free radicals and related ROS [e.g., Chatterjee, 1985;DeFeudis et al, 1985;Pincemail et al, 1989;Pietri et al, 1997;Soulie et al, 2002; see also reviews by DeFeudis, 1991DeFeudis, , 1998DeFeudis, , 2002Christen, 2000]. This ''oxidative stress'' that is overcome by EGb 761 occurs when free radicals and related ROS are present in excess and may be due to increased free radical formation and/or decreased activity of endogenous antioxidant activity.…”
Section: Antioxidant Effects Of Egb 761 In Relation To Stressmentioning
confidence: 98%